Information quality impact on firm's performance: Small and Medium Enterprises (SMES) in Bangladesh - Abdullah, Shahmir Sivaraj; Azim, Md. Shamimul (2015)
The challenge for Bangladesh today is how to make her existing SMEs better able to compete with their SME rivals from abroad.One way to overcome this challenge is by modernizing their operations with the inception of contemporary technologies into their production processes. Along with this comes the challenge of aligning and enhancing the prevalent culture and practices in line with the needs of these new industries so as to ensure not only survivability but also effectively compete globally. Globalization, as one knows, does not only have challenges but also enormous opportunities for those who have the capability of utilizing this phenomenon.The major issue that is implied for this to take place is the ability to adopt not only any technology but having the ability to choose the most appropriate technology. The primary purpose of this study is to investigate the impact of information systems on the performance of SMEs in Bangladesh which more often than not is related to technology adoption. To accomplish this objective, data was collected through the use of questionnaires from the samples which targeted the organizations operating in the industrial zone in Dhaka, Bangladesh. From the data analysis conducted the results indicate a positive relationship between information quality (IV1) and skills and knowledge (IV2) with the performance (DV) of SMEs in Bangladesh.